Exploring patient preferences for intraocular lenses selection in age-related cataract: a discrete choice experiment study - Zhu, Qiaolin; Sun, Qianqian; Huo, Yujia; Yang, Xiaoling; Huang, Hehe; Qian, Shanshan; Lin, Wenjing; Yan, Wentao (Frontiers in Medicine, 2025)
IntroductionThis study investigates the preferences of cataract patients in East China regarding intraocular lenses (IOLs).MethodsA Discrete Choice Experiment (DCE) was conducted using a questionnaire that included various IOLs attributes. Participants made choices based on different combinations of these attributes, and the data were analyzed using multinomial logit models (MNL) and latent class analysis (LCA) to identify preference heterogeneity.ResultsA total of 200 cataract patients (mean age 66.2 years, 58.5% female) participated in the study. The most influential factors in IOL selection were cost, followed by presbyopia correction, with a preference for multifocal IOLs (trifocal and bifocal), spherical aberration correction, and astigmatism correction. High cost and a higher probability of adverse visual phenomena negatively affected preferences. The inclusion of blue-blocking functionality and the surgeon’s recommendation had minimal influence on patient choice. LCA revealed three distinct preference groups: Class 1 (“Aberration Correction Seekers”) preferred aspheric IOLs, Class 2 (“Presbyopia and Blue-Blocking Enthusiasts”) favored multifocal IOLs, and Class 3 (“Astigmatism and Cost-Sensitive Patients”) preferred toric IOLs. Multinomial logistic regression analysis further showed that male patients were more likely to choose toric IOLs, while individuals with higher education levels were significantly less likely to prefer multifocal IOLs.ConclusionThis study highlights significant heterogeneity in cataract patient preferences for IOLs attributes. Cost was the most critical factor, followed by presbyopia and aberration correction. Men favored toric IOLs and exhibited sensitivity to cost, while highly educated individuals preferred multifocal IOLs less. These findings underscore the need for personalized IOLs recommendations and signal opportunities for innovation and customization in the IOLs industry.